Daya tangguh siswa SMA di Kabupaten Pangkajene dan Kepulauan - Faradillah Firdaus; Asmulyani Asri (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Adversity Quotient (AQ) is size or standard used todetermine the level of someone’s ability in cope with andsurvive against life’s problems and challenges. The ability toface all the difficulties is a process to build a personaldevelopment and potency, as well as to achieve goals.Adversity Quotient is intelligence possessed someone inovercoming difficulties and able to survive. AdversityQuotient is intelligence that arises because of pressure,difficulty and suffering. Stoltz argued that there are threeforms that can be translated from the Adversity Quotient as ameasurement of adversity intelligence, which is a conceptualframework in conducting the formulation to understand andimprove success. It is a measure for knowing individualsresponse patterns against difficulties and challenges, and theseries of skills that can be used in order to achieve a betterresponse in dealing with problems.